Analisis Historis Kanonisasi Sahih Bukhari-Muslim Oleh Al-Hakim Al-Naisaburi Pada Abad 5 Hijriyah - Fachruli Isra Rukmana; Abdul Haris; Sri Kurniati Yuzar (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2023)
This article discusses the role of al-Hakim al-Naisaburi in canonizing the sahih of Bukhari and Muslim and introducing them to hadith scholars so that the shahihain book becomes the authoritative hadith book in Islam. The development of hadith bookkeeping was carried out during the time of the Khalilah Umar bin Abdul Aziz in the 2nd to 3rd centuries AH, but the hadith books that had been collected were still considered ordinary books in general. Starting from this problem, the author formulated three problems which became the primary discussion in this research. a) what is the role of al-Hakim al-Naisaburi in carrying out the canonization process of the book of shahihain. b) how the existence of the shahihain book can become an authoritative source of Islamic law in Islam. c) what are the basic assumptions for the need for sharah evaluation of the authentic books of Bukhari and Muslim. The type of research applied in this analysis is qualitative research using a library research approach. Specifically, this research uses interpretive-historical analysis. The results of this research show that, from here the authentic books of Bukhari and Muslim became a reference to be used as a legal basis for Islamic school scholars, then the hadith scholars made the authentic books as a standard for writing hadith books and a standard for evaluating authentic hadiths thanks to al-Hakim al-Naisaburi. Therefore, Sahih Bukhari-Muslim is the main book of the Prophet's kalam heritage which must be preserved to this day